EFFECTS OF INTRATHECAL MIDAZOLAM IN SPINAL ANAESTHESIA: A PROSPECTIVE DOUBLE BLINDED CASE CONTROL STUDY - Abhishek, Kotalwar; Pankaj K, Roy; Prashant, Rai; Vikas, Tiwari; Manju, Jha (International Journal of Clinical and Biomedical Research, 2017)
Background: Increasing the duration of action and maximizing postoperative analgesia has always been a domain of interest in spinal blocks. Many adjuvants have been tried along with local anaesthetic agent to achieve the same. The following study was conducted to compare sensory and motor characteristics with 2mg midazolam in subarachnoid block. Aim: To evaluate the efficacy and analgesic effect of the mixture of 2 mg midazolam and 15 mg (3 ml) hyperbaric bupivacaine as compared to bupivacaine alone in patients undergoing infra-umbilical surgery under spinal block. Material and Methods: In this observational prospective case control study 100 patients (ASA class I and II), aged 18 to 55 years, undergoing elective infra-umbilical surgeries under spinal block were randomly divided into Group I- patients were administered 0.5% hyperbaric Bupivacaine (3 ml) + 0.9% Normal saline (0.4 ml) intrathecally and Group 2- patients were administered 0.5% hyperbaric Bupivacaine (3 ml) + 2mg preservative free Midazolam (0.4 ml) intrathecally. The onset and duration of sensory and motor block, hemodynamic variables, and side effects during the surgery and recovery were compared among the groups. Results: 2mg of preservative free midazolam used as an adjuvant to bupivacaine intrathecally reduces onset time of sensory and motor blockade, also time taken to reach T-10. It also increases time taken for two segmental recession and mean duration of analgesia. Conclusion: It can be inferred that Inj. Midazolam 2 mg in combination with Inj. bupivacaine 0.5% hyperbaric can be safely administered intrathecally for better postoperative analgesia. KEYWORDS: Intrathecal Midazolam; Post-operative Analgesia; Bupivacaine; Spinal Anesthesia.